2021
DOI: 10.1155/2021/8180424
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins as Markers for Monitoring Cancer Progression

Abstract: Lipoproteins are among the contributors of energy for the survival of cancer cells. Studies indicate there are complex functions and metabolism of lipoproteins in cancer. The current review is aimed at providing updates from studies related to the monitoring of lipoproteins in different types of cancer. This had led to numerous clinical and experimental studies. The review covers the major lipoproteins such as LDL cholesterol (LDL-C), oxidized low-density lipoprotein cholesterol (oxLDL-C), very low-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
(106 reference statements)
2
14
0
Order By: Relevance
“…Actually, the associations between HDL-c levels and tumorigenesis or cancer development have been reported in endocrine-related cancers, such as prostate cancer, epithelial thyroid cancer, ovarian cancer, pancreatic cancer, adrenal and testicular cancer [ 18 ]. Similar association is also observed in other malignant tumors, such as gastric cancer, hepatocellular carcinoma, and lung adenocarcinoma [ 19 ]. A recent study reported that HDL-c levels are associated with malignant intraductal papillary mucinous neoplasms (IPMNs) [ 20 ].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Actually, the associations between HDL-c levels and tumorigenesis or cancer development have been reported in endocrine-related cancers, such as prostate cancer, epithelial thyroid cancer, ovarian cancer, pancreatic cancer, adrenal and testicular cancer [ 18 ]. Similar association is also observed in other malignant tumors, such as gastric cancer, hepatocellular carcinoma, and lung adenocarcinoma [ 19 ]. A recent study reported that HDL-c levels are associated with malignant intraductal papillary mucinous neoplasms (IPMNs) [ 20 ].…”
Section: Introductionsupporting
confidence: 77%
“…Increasing evidence suggests that the cholesterol plays noticeable role in tumorigenesis and cancer progression [ 23 ]. Lipoproteins are also markers for monitoring cancer progression [ 19 ]. As one of the major components, HDL-c showed a meaningful correlation with cancer risk [ 24 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type of ω- Circulating lipids were similar to those of BC patients in the control arm of a newly diagnosed EPA/DHA supplementation study [27]. In the same way, Non-HDL and total cholesterol values were comparable to those described in a general population of agematched women [28].…”
Section: Type Of Studiessupporting
confidence: 72%
“…Conversely, some authors suggest a positive association between HDL-C and BC risk in women with extensive mammographic density [22]. However, as described by Maran et al [27] generally a significant association is strongly suggested between LDL-C and carcinogenesis and oxidized-LDL and metastasis.…”
Section: Type Of Studiesmentioning
confidence: 94%
“…Researchers revealed that statins showed a positive impact on the ICIs treatment outcome ( 13 ). The positive association of cancer risk and apoB level has been declared, while high LDL-C was suggested to be associated with high incidence of cancer and metastasis in most cancers ( 14 , 15 ). Recent studies indicated a positive correlation between LDL-C, HDL-C and serum cholesterol and the ICIs monotherapy response, whereas the contrary results were obtained in the chemotherapy groups ( 16 ).…”
mentioning
confidence: 99%